Effects of the Stacking Faults on the Electrical Resistance of Highly Ordered Graphite Bulk Samples - Andreas Hentrich; Pablo D. Esquinazi (C, 2020)
High anisotropy and the existence of two-dimensional highly conducting interfaces at stacking faults parallel to the graphene planes of the graphite structure influence, in a non-simple way, the transport properties of highly oriented graphite. We report two related effects on the electrical resistance of highly oriented pyrolytic as well as of natural graphite bulk samples, measured with the four points method in the temperature range 300 K <semantics>≤T≤</semantics> 410 K. A qualitative and quantitative change in the temperature dependence of the resistance was obtained by simply enlarging the electrodes and contacting the edges of the internal interfaces on the same sample. Additionally, at temperatures <semantics>T≳350</semantics> K the resistance can change with time. We show that this temperature-dependent annealing effect is related to the stacking faults and can irreversibly change the absolute value of the resistance and its temperature dependence. A partial recovery is obtained after leaving the sample at normal conditions for several days. The overall results stress the importance of the electrodes location on a bulk graphite sample, the contribution of the stacking faults in the interpretation of the measured transport properties and the need of systematic studies on the influence of high temperature annealing on the interfaces properties.